The Roles of Marketing Competencies, Product Innovation, and Decentralization in Driving Consumer Loyalty on Creative MSMEs - Nurhidayati, Safitri (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Indonesia’s creative industry, a key economic driver, faces challenges in marketing management competencies, impacting product innovation and consumer loyalty. This study explores how these competencies influence innovation and loyalty in subsectors like fashion, culinary, and handicrafts, with decentralization as a moderating factor. The objectives are to assess the effect of marketing management competencies on product innovation and consumer loyalty and to examine decentralization’s role in shaping business performance. A quantitative survey was conducted with 412 micro, small, and medium enterprises across 15 provinces, using Structural Equation Modeling for analysis. Findings show that marketing management competencies significantly enhance product innovation (β = 0.742, p < 0.001) and consumer loyalty (β = 0.658, p < 0.001), with product innovation mediating this relationship (indirect effect = 0.293, p < 0.01). Decentralization strengthens these effects in regions with robust local policies, with the Creative Marketing Competence Index revealing 67% higher innovation and 52% better retention for high-scoring enterprises. The study concludes that strengthening marketing competencies and leveraging decentralized policies are crucial for enhancing competitiveness in Indonesia’s creative industry, offering practical insights for enterprises and policymakers.